The Southeastern Librarian, Vol.46, No.2-4, Summer/Fall/Winter 1996 - Johnson, Theresa; Preuit, Catherine (The Southeastern Library Association, 1996)
The Southeastern Librarian, Vol.46, No.02-04, Summer/Fall/Winter 1996. Periodical.
1 electronic record. 60 pages. Scanned from original document. Contents Include: President's Message- 48, Editor's Note- 52, Thanks Claudia- 53, Kate W. Ragsdale- Limestone and Computers: Updating an Old Library Building to Accommodate New Services- 56, Lorraine D. Summers- SELA in Transition- 60, Judith Gibbons- The Tradition Continues: The 1996 Joint Conference- 64, SELA Reporters- Lexington in Review- 66, SELA Awards- 76, SELA Poster Sessions- 78, People- 83, Bulletin Board- 88, New and Useful- 89, Stateside View- 91, Calendar- 97, Volume 46 Index- 98, Guidelines for SELn Submissions- 46, 1996-1998 Officers and State Representative- 50, New Members- 87, Membership form- 100
Keywords: Periodicals | Southeastern Library Association